Burns and long-term infectious disease morbidity: A population-based study - Duke, J.; Randall, Sean; Wood, F.; Boyd, James H.; Fear, M. (Pergamon Press, 2016)
Background: There is a growing volume of data that indicates that serious injury suppresses immune function, predisposing individuals to infectious complications. With recent evidence showing long-term immune dysfunction after less severe burn, this study aimed to investigate post-burn infectious disease morbidity and assess if burn patients have increased long-term hospital use for infectious diseases. Methods: A population-based longitudinal study using linked hospital morbidity and death data from Western Australia for all persons hospitalised for a first burn (n=30,997) in 1980-2012. A frequency matched non-injury comparison cohort was randomly selected from Western Australia's birth registrations and electoral roll (n=123,399). Direct standardisation was used to assess temporal trends in infectious disease admissions. Crude annual admission rates and length of stay for infectious diseases were calculated. Multivariate negative binomial and Cox proportional hazards regression modeling were used to generate adjusted incidence rate ratios (IRR) and hazard ratios (HR), respectively. Results: After adjustment for demographic factors and pre-existing health status, the burn cohort had twice (IRR, 95% confidence interval (CI): 2.04, 1.98-2.22) as many admissions and 3.5 times the number of days in hospital (IRR, 95%CI: 3.46, 3.05-3.92) than the uninjured cohort for infectious diseases. Higher rates of infectious disease admissions were found for severe (IRR, 95%CI: 2.37, 1.89-2.97) and minor burns (IRR, 95%CI: 2.22, 2.11-2.33). Burns were associated with significantly increased incident admissions: 0-30days (HR, 95%CI: 5.18, 4.15-6.48); 30days-1year (HR, 95%CI: 1.69, 1.53-1.87); 1-10 years (HR, 95%CI: 1.40:1.33-1.47); >10years (HR, 95%CI: 1.16, 1.08-1.24). Respiratory, skin and soft tissue and gastrointestinal infections were the most common. The burn cohort had a 1.75 (95%CI: 1.37-2.25) times greater rate of mortality caused by infectious diseases during the 5-year period after discharge than the uninjured cohort. Conclusions: These findings suggest that burn has long-lasting effects on the immune system and its function. The increase in infectious disease in three different epithelial tissues in the burn cohort suggests there may be common underlying pathophysiology. Further research to understand the underlying mechanisms are required to inform clinical interventions to mitigate infectious disease after burn and improve patient outcomes.